Design and test of an adjustable quasi-zero stiffness device and its use to suspend masses on a multi-modal structure. (1st May 2021) - Shaw, A.D.; Gatti, G.; Gonçalves, P.J.P.; Tang, B.; Brennan, M.J.
Graphical abstract: Highlights: A mechanically simple quasi-zero stiffness device is designed, prototyped and tested. It is used to suspend masses on a structure avoiding shift of the resonant frequencies. It allows to statically load a slender structure while preserving its main dynamics. Applications include ground vibration testing for the aerospace industry. Abstract: In some applications, such as ground vibration testing in the aerospace industry, it is of interest to observe the modal behaviour of a slender structure while it is statically loaded. One way of statically loading such a structure is to suspend masses using very soft springs. If the springs are linear, then this results in an extremely large static deflection of the springs. This problem could be overcome by dynamically isolating the masses using quasi-zero stiffness (QZS) springs. This paper describes the design, construction and experimental testing of a device that can exhibit QZS. A novel design is proposed that allows the stiffness and the symmetry of the device to be adjusted independently using separate adjustment mechanisms. Quasi-static and dynamic testing of the device show that it can be adjusted to have an extremely low stiffness within the limits of measurement. The main trend of the force-displacement curve shows that it has a cubic stiffness characteristic, and that friction is responsible for its hysteretic behaviour. Dynamic testing shows that the device locks-up due to friction at low frequencies, but at high frequencies the device acts as an efficient linear isolator. An experiment was also performed where a mass was suspended on a multi-modal beam structure via the QZS device. It was shown that a static load could be applied to the beam without the attached mass appreciably affecting the dynamic response of the beam, even though the suspended mass was about 12% of that of the host structure.